A Comprehensive Review on Eugenol’s Antimicrobial Properties and Industry Applications: A Transformation from Ethnomedicine to Industry - Mak, Kit-Kay; Kamal, Masnah Banu; Ayuba, Sunday Buru; Sakirolla, Raghavendra; Kang, Yew-Beng; Mohandas, Kavitha; Balijepalli, Madhu Katyayani; Ahmad, Sazali Hamzah; Pichika, Mallikarjuna Rao (Pharmacognosy Reviews)
Eugenol and eugenol‑containing plants are used in ethno and modern medicine for various biological activities including antimicrobial activity. This review article provides an insightful transformation of eugenol from being an ethnomedicine to being a food protectant in the food industry. Scientific publications on the antimicrobial activity of eugenol and its respective advancements were collected from scientific databases such as Scopus, PubMed, and Google Scholar published between 1995 and June 2018. The eugenol has shown significant broad‑spectrum antimicrobial activities against Gram‑positive, Gram‑negative, fungi, and virus. The eugenol has also shown synergistic effects with conventional antimicrobials. Formulations, such as micro‑ and nanoemulsions, nanocapsules, and nanoparticles, are prepared to improve the aqueous solubility and efficacy of eugenol. Eugenol is used as a food protectant in storing plants, grains, fruits, and livestock. This review covers eugenol’s antimicrobial activities, formulations to improve aqueous solubility, and applications in the food industry. Extensive scientific investigations validated the ethnomedicinal uses of eugenol as an antimicrobial agent. Its activity on multidrug‑resistant pathogens should further be explored to identify the molecular mechanisms and synergistic/antagonistic effects with conventional antimicrobials. There were no studies on investigating eugenol’s potential in in vivo infectious animal models. This is the first review on eugenol that details the antimicrobial potential of eugenol and its possible applications as a protectant in the food industry.
Keywords: Antimicrobial; antiviral; essential oil; eugenol; food protectant; food industry